AN ERROR ANALYSIS IN WRITING DESCRIPTIVE TEXT AT ONE PRIVATE SCHOOL OF SINTANG - Henry Elisa; Sijono Sijono; Umi Umayah (Politeknik Negeri Bengkalis, 2022)
This research aims to classify the kinds of errors found in the student's writing descriptive text; recognize the most common errors found, and describe the factors that cause the students to make errors. The method used was qualitative research. The subject of this research is the 20 writing descriptive text of the students in class X. The data collection technique used documents and interviews. The instruments of data collection were the studentsâ€™ worksheets and interview guidelines. The finding showed, there were four types of errors found in the students' writing products. They were classified as 20.8% errors of omission, 4% errors of addition, 73,2% errors of misinformation, and 2% errors of misordering. Based on these findings, the researchers suggest that: learning English should emphasize linguistic aspects such as the use of tenses. Besides, students should be assisted in translating assignments and teachers should provide feedback on student work.Â Keywords: error analysis, descriptive text, writing